Quantitative geography the basics - Harris, Richard 1973- (Los Angeles Sage Publications, 2016)
"Written by world-leading experts, and balancing theory with application, the Spatial Analytics and GIS series provides a user-friendly introduction to these methods for students in the geosciences, geographical information science and quantitative social science."--Amazon.
About quantitative geography -- Foundations of quantitative geography -- Doing quantitative geography.
Includes bibliographical references (pages 289-296) and index.
Keywords: Geography -- Methodology; Geography -- Mathematics